Pelatihan Kanoko Shibori Pada T-Shirt Cotton Combed Di Pondok Pesantren Al – Ma’arij Jombang - Alfina Syifa Agustin (Pusat Riset dan Inovasi Nasional, 2024)
The Kanoko Shibori training at the Al-Ma'arij Jombang Islamic boarding school aimed at female students aims 1). Knowing the Kanoko Shibori training process at Al-Ma'arij Islamic Boarding School Jombang 2). Knowing the results of Kanoko Shibori's training products on Combed Cotton T-Shirts at Al-Ma'arij Islamic Boarding School Jombang 3). To find out participants' responses to the training process for making Kanoko Shibori on Combed Cotton T-Shirts at the Al-Ma'arij Islamic Boarding School in Jombang. The training, which was attended by 20 students, used a quantitative descriptive method with observation to determine the implementation of the learning process, then used a questionnaire method to determine student responses, and used a research instrument method to determine the finished product. The results of this research state that the implementation of the training process obtained final results of 85.4% for teacher activities and 87.5% for student activities in the very good category. The results of the training product, namely in the form of shibori on a Combed Cotton T-Shirt made by the participants, received an average result in motif clarity of 36% which means quite good, in color sharpness it got 41% which means very good and color absorption was 23% which means means good. The participants' response to the kanoko shibori training process on Combed Cotton T-Shirts reached 100% in the very good category. The research results show that the implementation of the Kanoko Shibori training at the Al-Ma'arij Islamic boarding school in Jombang is going well.